Enfleshed materialism in William Gibson’s The Peripheral: cyborgian bio-technological literary analysis - Najaf Ali Babazadeh; Razieh Eslamieh; Ayoub Dabiri (Penerbit Universiti Kebangsaan Malaysia, 2024)
The purpose of the present research is to analyze the cyborgian theories of decentered and nomadic subjects, trans-genetic organisms, trans-human, bio-discourse, bio-narrative and metamorphic becoming, employed by cyborg biotechnology to create enfleshed materialism. Cyborg develops the characters’ identity and the way they are linked to fictional reality and processes of creating the hybridized bodies. Gibson in The Peripheral (2014) portrays the non-unitary virtual subjectivities as well as challenges of genetic creatures through tracing the life of Flynne, the main protagonist. Donna Haraway, Paul Virilio and Rosi Braidotti are the selected theorists introducing the theory of the research; cyborg; an umbrella term referring to cybernetic organisms. Cyborg biotechnology expands the embodiment of the self and transforms the human into enfleshed body by making it cyborg, relating reader to the other worlds. In the cyborg biotechnology, the organic and non-organic bodies are produced through merging the body and non-body materials, relating to the debate on how cyborgian enfleshed body as an object of cyborg knowledge materializes, actualizes, shifts, and functions in bio-discourse. Cyborgian literary theory is used to examine virtual creatures, which are partly inorganic and partly machine to prove technology as a re humanizing power to claim agency over the enfleshed bodies.